Improvement of focusing performance for a multi-petawatt OPCPA laser facility. (26th September 2018) - Zhou, Kainan; Huang, Xiaojun; Zeng, Xiaoming; Xie, Na; Zuo, Yanlei; Guo, Yi; Jiang, Dongbin; Dai, Wanjun; Xue, Qiao; Huang, Wanqing; Li, Ende; Wei, Ling; et al.
Abstract: In the paper, we demonstrate improvement of the focused intensity for a multi-petawatt optical parametric chirped-pulse amplification laser facility by several methods. An adaptive optics system with a large-size deformable mirror is employed and it applies a closed-loop correction method based on detection of the on-target focal spot rather than wavefront. In addition, a pair of achromatic lenses is designed and utilized to compensate chromatic and spherical aberrations of the laser system. Moreover, the additional dynamic aberrations introduced by 3-stage optical parametric amplifiers are investigated experimentally. After optimization, the focal spot size (full width at half maximum, FWHM) is 3.3 µ m  ×  4.0 µ m in x -axis and y -axis directions and the enclosed energy in FWHM is 28% when an on-axis parabolic mirror with a focal length of 800 mm is used. The focused intensity of ~4  ×  10 21 W cm −2 has been achieved for a 1.6 PW shot. The laser intensity is expected to be 10 22 W cm −2 or higher for 4.9 PW peak power.